Living Pedagogy dalam Dolanan Anak: Studi Fenomenologis Interpretatif tentang Pembentukan Nilai Sosial dan Kebhinekaan pada Anak Usia Dini - Eko Suhendro (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study examines how early childhood education (ECE) teachers in Yogyakarta interpret and enact living pedagogy through dolanan anak to support children’s social and multicultural learning amid concerns that digitalization and modernization reduce opportunities for peer interaction and cultural learning.Methods – Interpretative Phenomenological Analysis (IPA) was employed. Eight purposively selected ECE teachers from several PAUD institutions participated. Data were generated through semi-structured in-depth interviews, participant observations of play-based learning sessions, and supporting documents (e.g., lesson plans and reflective notes). Analysis followed IPA procedures: iterative reading, initial noting, development of emergent themes, and cross-case interpretation.Findings – Dolanan anak functions as living pedagogy where values are embodied, negotiated, and practiced through play rather than transmitted via formal moral instruction. Teachers positioned dolanan as a “moral laboratory” for empathy, honesty, fairness, cooperation, and respect for difference. Five themes emerged: (1) dolanan as an ethical and emotional space, (2) teachers as cultural guardians and value mediators, (3) diversity as lived experience, (4) living pedagogy as embodied knowledge, and (5) pressures from modernization. Research Implications – Based on teachers’ meaning-making, the study conceptualizes living pedagogy as an embodied and dialogic value-formation process enacted in culturally grounded play. Traditional play should be positioned as a core pedagogical practice in ECE, supported by curriculum and school policy that balance technology use with local experiential learning.